2013
DOI: 10.1128/mcb.00262-13
|View full text |Cite
|
Sign up to set email alerts
|

Correct Assembly of RNA Polymerase II Depends on the Foot Domain and Is Required for Multiple Steps of Transcription in Saccharomyces cerevisiae

Abstract: bRecent papers have provided insight into the cytoplasmic assembly of RNA polymerase II (RNA pol II) and its transport to the nucleus. However, little is known about the mechanisms governing its nuclear assembly, stability, degradation, and recycling. We demonstrate that the foot of RNA pol II is crucial for the assembly and stability of the complex, by ensuring the correct association of Rpb1 with Rpb6 and of the dimer Rpb4-Rpb7 (Rpb4/7). Mutations at the foot affect the assembly and stability of the enzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 88 publications
10
51
1
Order By: Relevance
“…In addition, the partial dissociation of Rpb4/Rpb7 dimmer leads to an increase in mRNA stability by loss of mRNA imprinting [65,66]. Notably, all these defects are overcome by RPB6 overexpression and agree with previous data pointing to an important role of Rpb6 in RNA pol II integrity/assembly [47,[63][64][65].…”
Section: The Yeast Role In Medical Applications 154supporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the partial dissociation of Rpb4/Rpb7 dimmer leads to an increase in mRNA stability by loss of mRNA imprinting [65,66]. Notably, all these defects are overcome by RPB6 overexpression and agree with previous data pointing to an important role of Rpb6 in RNA pol II integrity/assembly [47,[63][64][65].…”
Section: The Yeast Role In Medical Applications 154supporting
confidence: 90%
“…Rpb6 and its bacterial homologue have been proposed to promote RNA pol II assembly and/or increase RNA pol stability, through specific interactions with the RNA pol II largest subunit, Rpb1, in the case of S. cerevisiae [53,56,63,64]. It has been recently reported that mutations in foot conserved domain of Rpb1 cause an integrity defect of the RNA pol II, altering the association between Rpb1 and Rpb6, and the correct association of the dimer Rpb4/7.…”
Section: The Yeast Role In Medical Applications 154mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, transcription of the C160-encoding gene is unaffected in this mutant (data not shown), so the largest Pol III subunit is probably degraded when unassembled to the complex. Nuclear degradation of the largest Pol II subunit by an Asr1-independent mechanism was detected in mutants defective in the assembly of the Pol II complex (47). Neither the mechanism of C160 degradation nor the location where this process occurs in rpc128-1007 cells is known, and this requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not detect obvious binding affinity between β-actin and Rpb6. A previous study showed that the Rpb6 subunit is part of a subcomplex that also contains two other subunits, Rpb7 and Rpb1 (Ishiguro et al 1998;Garrido-Godino et al 2013). We thus suspect that our results may stem from the fact that Rpb6 is located between Rpb7 and Rpb1, which prevents its interaction with other proteins.…”
Section: Discussionmentioning
confidence: 73%